Role of macrophage migration inhibitory factor in mice with sepsis and after effect of its intervention - Zhang, Zhen-hui (Zhongguo wei zhong bing ji jiu yi xue = Chinese critical care medicine = Zhongguo weizhongbing jijiuyixue, 2009)
OBJECTIVE: To investigate the expression profile of macrophage migration inhibitory factor (MIF) in serum and lung tissues of mice with sepsis, and to explore the effect of MIF antagonist ISO-1 on sepsis in a murine sepsis model